OWK zine - Panayides, Omiros (My University, 2026)
2018 Biennale of Western Balkans, Ioannina, GR, Part of the The Athens Zine Bibliotheque participation 2018 Livres d’ Artistes / Zampelas Art Museum, Nicosia